11x-112=4x-14

Simple and best practice solution for 11x-112=4x-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-112=4x-14 equation:


Simplifying
11x + -112 = 4x + -14

Reorder the terms:
-112 + 11x = 4x + -14

Reorder the terms:
-112 + 11x = -14 + 4x

Solving
-112 + 11x = -14 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-112 + 11x + -4x = -14 + 4x + -4x

Combine like terms: 11x + -4x = 7x
-112 + 7x = -14 + 4x + -4x

Combine like terms: 4x + -4x = 0
-112 + 7x = -14 + 0
-112 + 7x = -14

Add '112' to each side of the equation.
-112 + 112 + 7x = -14 + 112

Combine like terms: -112 + 112 = 0
0 + 7x = -14 + 112
7x = -14 + 112

Combine like terms: -14 + 112 = 98
7x = 98

Divide each side by '7'.
x = 14

Simplifying
x = 14

See similar equations:

| 1+5d=2d-5 | | 7x-154=2(1-3x) | | 10z+2z=12 | | -3x+10=3x+16 | | 3+m=5m-13 | | 2x+2=-33+7x | | 10x-13=6x+3# | | 6d-7=2d-23 | | -n+10=-5n-18 | | -5b+9=-24+6b | | 7t+9=41+3t | | -9-4m=4m-105 | | -1-m=6m-29 | | -4x+3=9+2x | | 6a+6=18+3a | | -2x-5=-6x+35 | | -a-3=-27+5a | | 5x-3=7x+13 | | -b-9=-4b+6 | | -3d+5=2d-45 | | -4d+5=4d-59 | | -3+3a=-2a+22 | | 2n-2=-7n+106 | | 7d+5=53+3d | | -a+1=-11+5a | | a-6=-14-3a | | 7t-4=68-5t | | 7d+5=11+6d | | 4(2y-y)=6(2y+8) | | Ax+bc=d | | 2a-5=7a-5 | | -6w+2=7w+145 |

Equations solver categories